Robot-Assisted Laparoscopic Radical Cystectomy and Modified Y-Shaped Ileal Orthotopic Neobladder Reconstruction - Mao, Weipu; Chen, Shuqiu; Zhang, Lijie; Li, Tao; Sun, Si; Xu, Bin; Zhu, Weidong; Zhang, Guangyuan; Zhang, Lei; Wu, Jianping; Chen, Ming (Frontiers in Surgery, 2022)
Background: Orthotopic neobladder reconstruction has become the preferred method of urinary diversion after radical cystectomy in major medical centers. We performed modified Y-shaped ileal orthotopic neobladder reconstruction and presented the functional results and postoperative complications of the modified surgery. Methods: We included 21 patients with bladder cancer who underwent radical cystectomy at our center between February 2019 and December 2019. All patients underwent robotic-assisted laparoscopic radical cystectomy and lymph node dissection plus modified Y-shaped ileal orthotopic neobladder reconstruction. We collected the demographic and pathological history of the patients, and perioperative and postoperative functional outcomes and postoperative complications were recorded. Results: All surgeries were successful and no serious postoperative complications occurred. The mean operative time was 321.43 ±54.75 min, including 101.67 ± 10.88 min required for neobladder reconstruction. Liquid intake was encouraged about 5 days after surgery, stent and catheter were removed after 13.52 ±3.28 days, and the patients were discharged 1-2 days after removing the catheter. No ureteral anastomotic and neobladder urethral anastomotic strictures occurred. The volume of the neobladder at 1-year post-surgery was 195.24 ±16.07 ml and the maximum urinary flow rate was 20.64 ±2.22 ml/s. Conclusion: We describe the robotic-assisted modified Y-shaped ileal orthotopic neobladder reconstruction performed at our center, which requires a simple suture and short neobladder construction time, minimizes the occurrence of anastomotic stenosis, facilitates smooth patient emptying, and is clinically scalable and applicable.